The Influence of Witley's Constructivist Model in Learning a Rapid Attack Collective for Students in Handball - Huda Majid Rashid (Journal of Global Pharma Technology, 2016)
The current study aims to identify the effect of Witley's constructivist model in learning the rapid collective-handball attack of students. The researchers used the experimental approach, while the research society included the fourth phase students (76) students. The research sample reached (60) students. Through the findings, the researchers reached several conclusions, the most important of which are:There is a positive development of the two groups in the study of learning rapid attack individual and collective handball.The experimental group that used the Witley's model is superior to the control group in the post tests.The educational units prepared by the researchers had a positive role in learning the rapid attack collective handball students of the experimental group and superior to the control group.Keywords: Witley's constructivist, Model, Rapid attack and handball.